Association of Quantified Costal Cartilage Calcification and Long-Term Cumulative Blood Glucose Exposure: The Multi-Ethnic Study of Atherosclerosis - Shabani, Mahsima; Pishgar, Farhad; Akhtarkhavari, Sepehr; Quinaglia, Thiago; Budoff, Matthew J.; Bluemke, David A.; Barr, Graham R.; Post, Wendy S.; Wu, Colin O.; Arbab-Zadeh, Armin; Sidhaye, Aniket; Lima, João A. C.; et al. (Frontiers in Endocrinology, 2021)
Aims: Anecdotal reports have suggested increased soft tissue calcification in individuals with long-term exposures to high blood glucose. The association of costal cartilage calcification (CCC), a reliably quantifiable marker obtainable from non-contrast cardiac computed tomography (CT) with cumulative FBG exposure, is unknown. In this study, we aimed to determine the association between quantified CCC and cumulative glucose exposure using non-contrast coronary artery calcium (CAC) scoring computed tomography (CT) images in the Multi-Ethnic Study of Atherosclerosis (MESA). Methods: The volume of bilateral CCC was quantified in high-density pixels (threshold of Hounsfield Unit>180) using the CAC scoring CT images acquired in the 5th MESA exam. Prior long-term cumulative exposure to fasting blood glucose (FBG) was calculated by area under the FBG-time curve over ten years before the time of the CT exam. Results: A total of 2,305 participants (mean age: 69, female/male: 1.3) were included in this study. The median CCC volume was lower in females than males (1158 mm3 [IQR: 1751] vs. 3054 mm3 [3851], p<0.001). In cross-sectional analysis, quantified CCC was associated with FBG (9% increase per SD) and HbA1c (6% increase per SD) at the CT exam only in female participants after adjustment for age, race, and BMI. Only in female participants, quantified CCC was also associated with prior cumulative FBG (2% increase per decile change). In the subgroup of females with zero CAC scores, the adjusted CCC was still associated with FBG (18% increase per SD) and HbA1c (12% increase per SD) at the time of CT exam and with prior cumulative FBG exposure (4% increase per decile change) before the CT exam. Conclusions: The CCC, a reliably quantified marker in non-contrast cardiac CT, is associated with 10-year cumulative FBG exposure only in female participants, even those with zero CAC.